Environmental Influences on Individuals with Autistic Spectrum Disorders with Special Emphasis on Seasonality: An Overview - George Botsas; Eirini Koidou; Konstantinos Chatzinikolaou; George Grouios (MDPI AG, 2023)
This paper offers an in-depth exploration of the intricate relationship between environmental factors and autism spectrum disorder (ASD), with a special emphasis on seasonality. It reviews existing research, providing a comprehensive summary of findings and highlighting the multifaceted dimensions of several environmental factors influencing the etiology of ASD. The discussion encompasses various elements, including birth months, maternal health, dietary choices, and vitamin D deficiency, delving into the intricate interplay of seasonality with environmental influences such as viral infections and solar radiation. The present study raises essential questions regarding the timing of environmental influences and the factors contributing to the rising prevalence of ASD. Ultimately, it underscores the need for future epidemiological research to incorporate more extensive investigations of environmental risk factors and employ advanced statistical analyses. This comprehensive overview contributes to a deeper understanding of how environmental factors, particularly seasonality, may be linked to the occurrence of ASD and its increasing prevalence, recognizing the multifaceted and diverse nature of these interactions.